THE TRANSFORMATIVE POWER OF ISLAMIC PRAYER: A QUALITATIVE INVESTIGATION OF SHALAT'S IMPACT ON ADULT WELL-BEING AND HAPPINESS - Esa Wahyu Nur Fadila; Ainun Evi Maisaroh (STAI Ma'had Aly Al-Hikam Malang, 2025)
This observational and interview-based study explores the effectiveness of shalat (Islamic prayer) in enhancing happiness among adults. Conducted with two primary subjects who regularly perform the five daily prayers, the study uses a qualitative approach through direct observation and semi-structured interviews, supported by significant others for triangulation. The findings reveal that consistent and mindful performance of shalat correlates with positive emotional, behavioral, and physical indicators of well-being. Subjects demonstrated calmness, gratitude, emotional regulation, and increased productivity after prayer. The study emphasizes shalat not only as a religious obligation but also as a spiritual practice that contributes to psychological resilience and subjective well-being. These results suggest that spiritual practices like shalat can serve as valuable tools for mental health and happiness in adults, providing a meaningful avenue for further research in religious psychology and emotional wellness.